Nudging in the workplace: Increasing participation in employee EDI wellness events - Diane Pelly; Orla Doyle (University College Dublin, UCD School of Economics, 2022)
Organisations are investing significant resources in promoting the physical, emotional, and psychological well-being of their employees. In hybrid working environments, virtual worker wellness events are increasingly being used to combat social isolation and boost employee morale. Yet attendance at such events is often low. Using a randomised control trial, this study tests whether four behaviourally informed nudges (i) simplification, (ii) changing the messenger, (iii) using social proof and (iv) setting a default, can increase the registration and attendance rates of 6,998 public sector employees at three EDI (Equality Diversity Inclusion) wellness events. We find evidence that defaults matter. Pre-registering employees more than trebles the attendance rate, from 2.8% to 9.5%. While providing social proof and changing the messenger increase registration rates, they have no impact on attendance. We find little evidence of treatment heterogeneity, suggesting that defaults may have wide applicability. Our results have important implications for organisations seeking to enhance the impact and return on investment of their worker wellness initiatives.
Keywords: D91; I31; C93; M14; 330; behavioural economics; nudge; RCT; worker well-being; defaults